BBC micro:bit recipes : learn programming with Microsoft MakeCode Blocks - Seneviratne, Pradeeka (Technology in action series., 2019)
Build engaging programs for the BBC micro:bit using Microsoft's MakeCode web editor. Using this open source platform, you'll learn to program in an accessible way that easily translates into real-world programming. BBC micro:bit Recipes is a practical guide with a problem-solving approach. It provides exact solutions for common application development problems for the micro:bit using MakeCode. You'll discover and apply techniques that can be used to build simple games with sprites, keep score, and control game play. The micro:bit is a small programmable device that is a cross between a very small computer and a programmable embedded board. It is easy to program, extremely versatile, and designed with young learners in mind. In particular, it is designed to be easy for people who have never programmed before. By the end of this book, you'll have the foundation to build programs with the Microsoft MakeCode editor and use and process data with the built-in sensors, such as accelerometer, compass, temperature, touch, and light. You'll also see how to work with communication protocols, such as Serial, I2C, and SPI and how to use variables, loops, logic, arrays, math and functions to easily solve problems.- Resumé vydavatele